Mengakhiri Kemiskinan: Langkah Menuju Dunia yang Lebih Setara dalam Perspektif Filsafat Pendidikan Kristen - Deak, Victor (Indo Publishing, 2025)
Poverty is a multidimensional issue that involves not only economic deprivation but also social, moral, and spiritual aspects. Efforts to eradicate poverty form an essential part of the Sustainable Development Goals (SDGs), which require the participation of all sectors, including educational institutions and religious organizations. This study aims to analyze the role of Christian education and educational philosophy in fostering awareness, character, and social action oriented toward justice and equality. Using a descriptive qualitative approach, the research examines the relationship between biblical values-such as love, justice, solidarity, and service-and philosophical thought in education. The findings indicate that Christian education contributes to shaping faith sensitivity and moral responsibility toward the poor, while educational philosophy cultivates critical and rational awareness in confronting social injustice. The integration of these two perspectives gives rise to a holistic and transformative educational approach that encompasses intellectual, moral, spiritual, and social dimensions. This study emphasizes that poverty alleviation is not solely an economic or governmental task but also a calling of faith and an educational mission to humanize humanity. In the context of the modern era-marked by social inequality and globalization-the collaboration between faith, knowledge, and social action becomes the key to creating a more just, equitable, and humane world.